PHYSIOTHERAPY PROGRAM IN POST-OP CORONARY ARTERY BYPASS GRAFT (CABG) PATIENTS: CASE REPORT - Fauzia Riska Saputri; Wijianto; Purnomo Gani; Diani Qomara Dewi (CV. Fahr Publishing, 2024)
CABG is a surgical operation performed by creating new blood vessels or bypassing blocked blood vessels so that the blood flow carrying oxygen to the heart muscle supplied by the vessels is smoothed again. The study aimed to determine the management of physiotherapy in CABG cases. The research method used a case report method conducted on a 64-year-old male patient with a medical diagnosis of post-CABG surgery 4 Grafft A. I CAD3VD With Lm Disease, CTO at Prox RCA, complained of pain in the chest (surgical incision), ineffective breathing patterns, difficulty coughing, and the patient felt that his upper and lower limb movements were still limited. Physiotherapy interventions were conducted in 5 meetings from November 8, November 11, and November 12, November 13, to November 15, 2024. Starting from observation to evaluation. The physiotherapy Intervention given is a Breathing exercise (deep breathing exercise), effective coughing exercise with ACBT huffing), stretching of upper and lower limbs, and gradual mobilization. Measurements are made with a Sphygmomanometer, pulse oximeter, thermometer to measure vital signs during pre-post action, NRS (numbering rating scale) for pain, Meter line for thoracic expansion, and ICUMS for functional ability activities. The results showed a significant decrease in motion pain and still pain, where motion pain decreased from NRS 7 to NRS 0, as well as an increase in thoracic expansion, where the difference in breathing when inhaling and exhaling increased the thoracic cage from a difference of 0.8 cm to 2.8 cm, and an increase in functional ability. Using ICUMS, an increase in functional ability on the first day got a score of 10 (All activities are done above the bed) until the final evaluation got an ICUMS score of 10 (walking independently).